Fake Images, Real Effects: Deepfakes as Manifestations of Gender-based Political Violence - Barrientos-Baez, Almudena; Otero, Teresa Pineiro; Reno, Denis Porto [UNESP] (Historia Sistemas Informativos -hisin, 2024)
Introduction: The study addresses the issue of deepfakes and their effect on public perception, highlighting their evolution from ancient practices of visual manipulation to becoming advanced tools for constructing alternative realities, particularly harmful to women. The use of image manipulation as a form of attack or repression leads to considering this practice as part of violence against women in politics. Methodology: This exploratory study delves into the use of manipulated images against female politicians. For this purpose, a multiple methodology was designed: interviews with female politicians, analysis of fake images audited by factcheckers, and simple searches on adult content platforms. Results: The study reveals the use of fake images as a way to attack and discredit female politicians, predominantly consisting of cheapfakes. Discussion: The limited sophistication in the manipulation of images of female politicians allows for the detection of forgeries by a critical audience. Conclusions: The conclusions underscore the need for media literacy to combat misinformation and confirmation bias. The research emphasizes gender violence in politics, where deepfakes are used to silence and discredit women, thus perpetuating misogyny and the maintenance of existing power structures.
Keywords: Deepfake; Image manipulation; Misogyny; Politics; Disinformation; Pornography; Violence against women in politics